The Resilience of Antarctic Treaty System in the XXI Century: Procedural and Institutional Legitimacy - Patrizia Vigni; Yelena Yermakova (The Yearbook of Polar Law Online, 2024)
This article analyses the internal functioning of the Antarctic Treaty System (ATS) in light of present challenges such as new diverse and growing activities in the Antarctic. Specifically, the authors assess whether the ATS is capable of ensuring the effective management of the Antarctic region by looking at the internal legitimacy of the ATS. The internal legitimacy of the ATS is broken into procedural and institutional legitimacy. The authors discuss the following characteristics of the system: participation in the decision-making, accountability and transparency of legislative procedures and acts, and the institutional apparatus.